The Significance of tabnith in the Context of Correspondence of Heavenly and Earthly Sanctuary in Exodus 25:9, 40 - Abin, Blasius (Klabat Theological Review, 2020)
The picture of the heavenly sanctuary/temple is that of a model for the construction of the earthly counterpart. This understanding is conveyed mainly by the concept of תַּבְנִ֣ית , “pattern, form, or model” in Exod 25:9, 40 or σκιά , “shadow” in Heb 8:5, or ὑπόδειγμα , “copy” in Heb 9:23, 24. It reveals that the heavenly sanctuary functions as the archetype of the earthly temple. In the context of the book of Exodus, תַּבְנִ֣ית functions as the model of the sanctuary Moses was to build on the earth. Moses was probably shown the heavenly sanctuary and a “model” of what he had to build upon the earth. The תַּבְנִ֣ית thus presupposes an original reality and, at the same time, also suggests an idiomatic correspondence between the heavenly sanctuary and its earthly counterpart. Keywords: pattern; heavenly sanctuary; earthly sanctuary